PEDAGOGICAL EFFECTIVENESS OF USING AI TOOLS (CHATGPT, CLAUDE) IN ENGLISH LANGUAGE LESSONS IN TECHNICAL SCHOOLS (Ustozlar uchun, 2026)
This article analyzes the pedagogical effectiveness of using artificial intelligence-based tools, in particular the ChatGPT and Claude platforms, in English language lessons in technical schools. The study highlights the potential of AI tools to develop students' language skills, organize independent learning, increase motivation, and provide an individual approach. It also examines mechanisms for improving the quality and efficiency of education as a result of integrating these technologies into the educational process. The article analyzes the advantages of using AI tools, as well as possible problems and ways to overcome them. The results obtained are important for the modernization of English language teaching in technical schools and the improvement of digital pedagogical approaches.